Use of Handheld Ultrasound to Estimate Fluid Status of Hemodialysis Patients (Nepalese Medical Journal, 2018)
Introduction: Accurate assessment of fluid status in hemodialysis patients presents a significant challenge. Nephrologists have long relied on dry weight estimation based solely on clinical parameters to decide the ultrafiltration volume for patients with end-stage kidney disease on dialysis. However, this method is far from accurate and many patients recurrently suffer from signs and symptoms of fluid overload or circulatory collapse from overaggressive ultrafiltration. Invasive methods such as measurement of central venous pressure cannot be used routinely. We evaluated the usefulness of inferior vena cava (IVC) diameter measured by handheld ultrasound in the estimation of fluid status in patients before and after hemodialysis. Materials and Methods: Clinical assessment included patients’ symptoms, weight, blood pressure, heart rate, and presence of edema before and after dialysis session. Dry weight was assessed based on the above parameters. Each patient underwent measurement of inferior vena cava before and after hemodialysis. The anteroposterior IVC diameter (IVCD) was measured 1.5 cm below the diaphragm in the hepatic segment in supine position during normal inspiration and expiration.Results:  Thirty hemodialysis patients (mean age 51.6±18.03 years) were evaluated in outpatient dialysis unit. Following hemodialysis mean IVCe (IVC diameter in expiration) decreased from 1.40±0.38 to 0.91±0.30 cm (p